PAPAIN INDUCED PROGRESSIVE DEGENERATIVE CHANGES IN ARTICULAR CARTILAGE OF RAT FEMOROTIBIAL JOINT AND ITS HISTOPATHOLOGICAL GRADING - H. M. Khan; M. Ashraf; A. S. Hashmi; M. U. D. Ahmad; A. A. Anjum (Journal of Animal and Plant Sciences, 2013)
Osteoarthritis (OA) is a chronic debilitating disease of articular joints in human beings and animals. Severity of this drastic malady relate directly with extent of changes at molecular level in affected joint. Progressive structural changes in knee joint cartilage during development of OA were graded using modified Mankin scoring system. OA was induced in male Wister rats (n=25) by injecting papain (10mg/joint) and compared with control group of rats (n=5) receiving sterile saline solution. Papain injected rats were divided into five groups (n=5) and sacrificed under high dose of anesthetic ether after 1 st, 7 th, 14th, 21st and 28th days. OA and control knee joints were removed and extent of histological changes in cartilage structure was assessed. Histological features of rat cartilage included were surface layer, population of chondrocytes, orientation of chondrocyte columns, morphology of cells and matrix. Score was allocated based on the severity of changes occurred in cartilage micro-texture in relation to time. Highest histological lesion score (12.82±1.64) was observed in papain induced OA cartilages on 28th day followed by 10.09±2.02 (21st day), 9.92±2.76 (14th day), 7.48±1.15 (7th day) and 3.09±.81 (1st day), respectively. Severity of lesions progressed with passage of time and maximum lesions were observed on day 28. Findings recorded after 28th day of papain injection seem to be consistent and resemble with early phase of OA in human articular cartilage. This method offers a rapid and minimally invasive method to produce OA like lesions in rodent model. Grading system will provide insight to chalk out therapeutic strategies for early OA.
Keywords: Osteoarthritis; Papain; Knee joints; histological lesions and cartilage